DESAIN PEMBELAJARAN LUAS DAERAH SEGITIGA PADA PENDEKATAN SAINTIFIC - Mulyani Mulyani (Universitas Islam Nusantara, 2021)
This research is background by the emergence of learning barriers (learning obstace) which is epistemological. This research is a qualitative research by using research methods of didactic design (Disactical Design Research). The data collection techniques in this research is using triangulation with learners in the 4-third grade as a research subjects to identify learning obstacle, and the students of class 1-first grade for the implementation of the didactic design. The results showed that there is a learning obstace on the concept of pedestal partner and triangle high, then didiactic design arranged based on learning obstacle and relevant learning theories, in general response that had been given by learners appropriate with predictions, and the didactic design is potentially to be able to develop the ability of conceptual understanding.